Utilization of Tigernut Milk in Yoghurt Production: Physicochemical Properties and Growth of Lactobacillus bulgaricus and Streptococcus thermophiles in Tigernut Yoghurt. (IPS Journal of Nutrition and Food Science, 2024)
This study investigated the physicochemical properties and growth of Lactobacillus bulgaricus and Streptococcus thermophiles in tigernut yoghurt. Yoghurt was produced from 3 sets of milk namely 100% tigernut milk, 50:50% of tigernut milk and cow milk; and 100% of cow milk. A set coded: TMYs, TCMYs and CMYs was sweetened with sugar and another set coded: TMYd TCMYd and CMYd was sweetened with date. Pasteurized milk samples were inoculated with the starter culture (1% w/v) and incubated at 43 °C for 6 and 12 h. Sample were analyzed using standard methods. pH decreased significant (P
Keywords: Tigernut; Yoghurt; Lactobacillus bulgaricus; Streptococcus thermophilus; physicochemical properties; Growth rate